Simplified human phantoms for narrowband and ultra-wideband body area network modelling. Issue 2 (2nd March 2015) - Slawomir Wiak, Professor; Januszkiewicz, Łukasz; Hausman, Sławomir
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to compare the properties of simplified physical and corresponding numerical human body models (phantoms) and verify their applicability to path loss modeling in narrowband and ultra-wideband on-body wireless body area networks (WBANs). One of the models has been proposed by the authors. Design/methodology/approach – Two simplified numerical and two physical phantoms for body area network on-body channel computer simulation and field measurement results are presented and compared. Findings – Computer simulations and measurements which were carried out for the proposed simplified six-cylinder model with various antenna locations lead to the general conclusion that the proposed phantom can be successfully used for experimental investigation and testing of on-body WBANs both in ISM and UWB IEEE 802.15.6 frequency bands. Research limitations/implications – Usage of the proposed phantoms for the simulation/measurement of the specific absorption rate and for off-body channels are not within the scope of this paper. Practical implications – The proposed simplified phantom can be easily made with a low cost in other laboratories and be used both for research and development of WBAN technologies. The model is most suitable for wearable antenna radiation pattern simulation and measurement. Social implications – Presented results facilitate applications of WBANs in medicine and health monitoring. Originality/value – A new six-cylinder phantom has been proposed. The proposed simplified phantom can be easily made with a low cost in other laboratories and be used both for research and development of WBAN technologies.